LA "CEPA PAQUERA", UNA CEPA DE REFERENCIA DE BOOPHILUS MICROPLUS PARA PRUEBAS DE RESISTENCIA CONTRA ACARICIDAS EN COSTA RICA - Lambert, Gorissen (1979)
A susceptible strain, continuously cultivated in the laboratory, is essential for the realization of resistance tests with Boophilus micro plus. Ticks collected on a farro in Paquera, Guanacaste, were sent to the Wellcome Laboratories in England for being tested against organic phosphate compounds. The ticks appeared to be completely susceptible to these acaricides, as well as against carbaryl. The strain is now maintained in the laboratory in San Isidro de Coronado as the reference strain of B . microplusfor Costa Rica. The technique of the "Shaw test", in which larvae of the proper age are used for determining the susceptibility of ticks against acaricides, is now well established in our laboratory and we hope to start soon with a systematic investigation, of the efficiency of the acariddes used in Costa Rica against B. miáoplus. The problem of a possible ressistance of B. microplus in Costa Rica and the importance of a tick-resistance laboratory in case of a resistance outbreak have been discussed.